Streptomycessp. MUM273b: A mangrove‐derived potential source for antioxidant and UVB radiation protectants - Tan, L. T. H.; Mahendra, C. K.; Yow, Yoon Yen *; Chan, Kok Gan; Khan, T. M.; Lee, L. H.; Goh, B. H. (Wiley Open, 2019)
Microbial natural products serve as a good source for antioxidants. The mangrove‐derived Streptomyces bacteria have been evidenced to produce antioxidative compounds. This study reports the isolation of Streptomyces sp. MUM273b from mangrove soil that may serve as a promising source of antioxidants and UV‐protective agents. Identification and characterization methods determine that strain MUM273b belongs to the genus Streptomyces. The MUM273b extract exhibits antioxidant activities, including DPPH, ABTS, and superoxide radical scavenging activities and also metal‐chelating activity. The MUM273b extract was also shown to inhibit the production of malondialdehyde in metal‐induced lipid peroxidation. Strong correlation between the antioxidant activities and the total phenolic content of MUM273b extract was shown. In addition, MUM273b extract exhibited cytoprotective effect on the UVB‐induced cell death in HaCaT keratinocytes. Gas chromatography–mass spectrometry analysis detected phenolics, pyrrole, pyrazine, ester, and cyclic dipeptides in MUM273b extract. In summary, Streptomyces MUM273b extract portrays an exciting avenue for future antioxidative drugs and cosmeceuticals development.